Is native quantitative thought concretized in linguistically privileged ways? A look at the global picture. Issue 5 (17th August 2020) - Everett, Caleb
ABSTRACT: This work investigates whether reference in speech to certain quantities, namely 1, 2, and 3, is privileged linguistically due to our brain's native quantitative capacities. It is suggested that these small quantities are not privileged in specific ways suggested in the literature. The case that morphology privileges these quantities, apart from 1, is difficult to maintain in light of the cross-linguistic data surveyed. The grammatical expression of 2 is explained without appealing to innate quantitative reasoning and the grammatical expression of 3 is not truly characteristic of speech once language relatedness is considered. The case that 1, 2, and 3 are each privileged lexically is also difficult to maintain in the face of the global linguistic data. While native neurobiological architecture biases humans towards recognizing small quantities in precise ways, these biases do not yield clear patterns in numerical language worldwide.